Engendering Nationality: Haudenosaunee Tradition, Sport, and the Lines of Gender - Downey, Allan (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2012)
The Native game of lacrosse has undergone a considerable amount of change since it was appropriated from Aboriginal peoples beginning in the 1840s. Through this reformulation, non-Native Canadians attempted to establish a national identity through the sport and barred Aboriginal athletes from championship competitions. And yet, lacrosse remained a significant element of Aboriginal culture, spirituality, and the Native originators continued to play the game beyond the non-Native championship classifications. Despite their absence from championship play the Aboriginal roots of lacrosse were zealously celebrated as a form of North American antiquity by non-Aboriginals and through this persistence Natives developed their own identity as players of the sport. Ousted from international competition for more than a century, this article examines the formation of the Iroquois Nationals (lacrosse team representing the Haudenosaunee Confederacy in international competition) between 1983-1990 and their struggle to re-enter international competition as a sovereign nation. It will demonstrate how the Iroquois Nationals were a symbolic element of a larger resurgence of Haudenosaunee “traditionalism” and how the team was a catalyst for unmasking intercommunity conflicts between that traditionalism—engrained within the Haudenosaunee’s “traditional” Longhouse religion, culture, and gender constructions— and new political adaptations.